Optimization of Combined Catalytic Ethanolysis of Ceiba pentandra (L.) Seed Oil and Analysis of Metal Trace Elements in Produced Biodiesel - Montcho, Papin Sourou; Avocefohoun, Alphonse S.; ADJOU, EULOGE SÈNAN; YOUSSAO ABDOU KARIM, ALASSANE; AGBANGNAN DOSSA, COKOU PASCAL; Chrostowska, David Bessieres, Anna; Bessieres, David; AVLESSI, FÉLICIEN; SOHOUNHLOUE, KOKO CODJO DOMINIQUE (My University, 2022)
Ethanolysis of seeds oil from Ceiba pentandra with ethanol in combined catalysis was investigated in this study. In addition, the metal trace elements (TMEs) of the formulated biodiesel were quantified. For this purpose, the formulation of ethyl esters was done in two steps (acidic and basic) followed by purification. The influence of the molar ratio of ethanol to oil (6:1-8:1), the ratio of the mass of catalyst to oil (1.0; 1.1; 1.25 and 1.5) and the reaction temperature (30-60)°C were studied in order to optimize the operating conditions of this reaction. Subsequently, part of oil was converted to ethyl esters with the optimal reaction parameters. The analysis of metal trace elements using inductively coupled plasma mass spectrometry (ICP-CRC-MS, Agilent 7500) lead to determine the metal trace elements in both samples (oil and biodiesel) after mineralization. Calibration was performed with aqueous standards to avoid the use of organic standards which are often unstable. Fatty acids in the oil were converted into ethyl esters under optimal conditions (ethanol/oil molar ratio of (40:1), the amount of catalyst (H2SO4) (10% w/w) and a temperature of 78°C) for a fatty acid content equal to 0.46% (w/w). Triglycerides in oil were transesterified under basic catalysis with the optimal operating conditions (ethanol/oil molar ratio = 6:1, amount of catalyst = 1.1% (w/w) and reaction temperature = 60°C) yielded of improved ethyl esters equal to 98.91% (w/w). The MTEs of the vegetable oil samples and the formulated biodiesel revealed relatively low concentrations. On the other hand, other TMEs (Mg, Na, K and Ca) were quantified with concentrations that are higher (sup 0.1 μg/Kg) but lower than the recommended value (<500 μg/Kg) (ASTM D6751/ EN 14214). Data recovery was in the range of 90 to 100% for the two samples studied.
Keywords: Ethanolysis; Combined catalysis; Metal trace elements; Vegetable oil; Formulated biodiesel; Ceiba pentandra; ICP-MS